Analysis and Construction of Software Engineering OBE Talent Training System Structure Based on Big Data. (30th July 2022) - Jie, Zhang
Abstract : Software engineering is one of the most active fields of entrepreneurship and innovation in the world, and it is also the core field of the information technology industry. Software talents as the foundation and support are an important weight to determine the future direction of my country's software engineering. How to make colleges and universities cultivate compound software talents with innovative ability and engineering ability and how to guide students to closely combine innovative thinking with social practice are a major challenge faced by the current software process education in colleges and universities in my country. At present, the overall quality of software engineers is poor, which cannot meet the needs of enterprises and training objectives. This paper puts forward the application of the OBE (outcome-based education) model in the training of software talents, which can effectively solve the current problems of talent quality and social demand. The analysis shows that there is a high correlation between collaborative education and satisfaction, and the collaborative education model can effectively improve satisfaction. The investment of scientific research funds can effectively improve the overall quality of scientific research team members. The OBE talent training mode can effectively improve the overall test effect, whether in the experimental set or the test set, the test result of the OBE talent training structure is still the highest, the accuracy rate can reach 94.23%, the recall rate can reach 94.51%, and the F1 value can reach 95.13%. It is fully explained that the identification accuracy is the highest when the OBE talent-training structure is adopted.